2020
DOI: 10.1021/acsabm.9b00781
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic Chain Modification of Collagen Type I: Development of Elastomeric, Compliant, and Suturable Scaffolds

Abstract: Collagen type I is one of the most suitable natural biomaterials for constructing tissue-engineering scaffolds. Despite their biocompositional similarities to physiological tissues, these scaffolds lack host specific and matching mechanical properties. While it is possible to enhance their stiffness by cross-linking, it often compromises their abilities to expand or strain under minimal stress, that is, compliance (inverse of stiffness). Here, we report a simple, inexpensive, cross-linking-and elastinfree coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The comparison between the 1 H NMR spectra of the individual components, i.e. Coll I and 3,4-DB, and their conjugate showed that the signal of the proton from the aldehyde group of 3.4-DB (δ = 9.5 ppm) disappear in the Coll-Cat spectrum and the peaks corresponding to the aromatic protons of 3,4-DB (δ = 7-7.5 ppm) and Coll I as well as the protons associated with the aliphatic group from Coll I were shifted, which indicates the formation of the conjugate [31].…”
Section: Resultsmentioning
confidence: 99%
“…The comparison between the 1 H NMR spectra of the individual components, i.e. Coll I and 3,4-DB, and their conjugate showed that the signal of the proton from the aldehyde group of 3.4-DB (δ = 9.5 ppm) disappear in the Coll-Cat spectrum and the peaks corresponding to the aromatic protons of 3,4-DB (δ = 7-7.5 ppm) and Coll I as well as the protons associated with the aliphatic group from Coll I were shifted, which indicates the formation of the conjugate [31].…”
Section: Resultsmentioning
confidence: 99%
“…To study scaffold morphology, SEM was performed in accordance with an earlier published protocol. 29 In brief, scaffolds were fixed overnight at 4 °C in 2.5% glutaraldehyde in 100 mM sodium cacodylate buffer and 0.1% tannic acid (pH 7.2−7.4). Samples were washed with a 100 mM sodium cacodylate buffer with 3% sucrose and 3.0 mM MgCl 2 .…”
Section: Contact Angle Measurements and Scanning Electron Microscopymentioning
confidence: 99%
“…The percentage of free amine groups in dECMs was determined using 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay, as described in our previous work. 29 Briefly, unmodified and modified dECMs were dried, weighed, and reacted for 2 h with a mixture of 500 μL of 4.0% w/v NaHCO 3 aqueous solution and 500 μL of 0.05% w/v TNBS at 40 °C. The reaction was quenched with 6 M HCl and left for reaction for 1.5 h at 60 °C.…”
Section: ■ Introductionmentioning
confidence: 99%